Prevalence and clinical implications of major and minor ANCAs in Tunisian (North African) patients with systemic lupus erythematosus - Meddeb, Zeineb; Abida, Houssem; Krir, Dhouha; Ben Hmid, Ahlem; Aouaidia, Raja; Abdelkéfi, Cherifa; Nasri, Yosra; Ben Sghaier, Ines; Kebaier, Hayet; Samoud, Samar; Goucha, Rim; B’Chir Hamzaoui, Saloua; et al. (Frontiers in Immunology, 2025)
IntroductionAnti-neutrophil cytoplasmic antibodies (ANCAs) have been reported in systemic lupus erythematosus (SLE). Their clinical significance remains unclear especially in the African populations. This study aimed to assess the prevalence, antigenic targets, and clinical correlations of ANCAs in SLE patients in a Tunisian (North African) cohort. MethodsWe conducted a cross-sectional case-control study involving 30 patients with systemic lupus erythematosus (SLE) and 30 healthy controls. Blood samples were screened for antineutrophil cytoplasmic antibodies (ANCAs) using indirect immunofluorescence (IIF) (FA 1201-1005-13, Euroimmun®). Enzyme-linked immunosorbent assay (ELISA) (Euroimmun®) was performed on IIF-positive samples to assess six ANCA antigenic targets: proteinase 3, lactoferrin, myeloperoxidase, elastase, cathepsin G, and bactericidal/permeability-increasing protein (BPI). Clinical and immunological evaluations were conducted for all SLE patients at the time of the study. No ANCA- associated vasculitis-SLE overlap cases were identified.Results and discussionANCAs were detected in 16 of 30 SLE patients (53%) and in 1 of 30 healthy controls (3%). Among the ANCA-positive patients, nine showed reactivity to lactoferrin, while the antigenic target remained undetermined in 7 cases. The median SLEDAI-2K score at inclusion was 8 [1.75–12]. In univariate study, ANCA positivity was significantly associated with acute cutaneous manifestations (p=0.021), lupus nephritis (p=0.001), as well as use of glucocorticoids (p=0.014) and mycophenolate mofetil (p=0.009). Besides, it was associated with lower C3 (p=0.0036) and C4 (p=0.0032) titers and higher anti-dsDNA titers (p<0.0001). In multivariate analysis, ANCA positivity was correlated to anti-ds DNA (p=0.008). When comparing anti-LF positive and anti-LF negative patients, univariate analysis found an association with articular involvement (p=0.011), renal activity index (p=0.036) and ELISA titers (p=0.0004). ANCAs were frequent in our SLE cohort, with lactoferrin as the only identifiable antigenic target, unlike previous reports, which suggests a role to ethnicity and environment components. Their presence was associated with higher disease activity and more severe renal involvement.